2018
DOI: 10.1002/jcp.27046
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid inhibits nicotine‐induced C‐reactive protein generation by inhibiting NLRP3 inflammasome activation in smooth muscle cells

Abstract: Atherosclerosis is widely known to be a chronic inflammatory disease. C-reactive protein (CRP), an important inflammatory factor, plays an essential role in the pathogenesis of atherosclerosis. Nicotine, the main addictive component of cigarette, has been shown to induce the production of CRP. The aim of this study was to investigate the effect of rosmarinic acid (RA), a polyphenol with antiinflammatory activity, on nicotine-induced elevation of CRP in vascular smooth muscle cells (VSMCs). We found that pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Besides this, it also attenuates cardiac fibrosis in long-term pressure overload via AMPKα/Smad3 Signalling (Zhang et al, 2018). Yao et al (2019) reported that rosmarinic acid inhibits NLRP3 inflammasome activation, resulting in reduced CRP generation in vascular smooth muscle cells. Rosmarinic acid also alleviated cardiomyocyte apoptosis by inhibiting the expression and release of Fas L in cardiomyoblast via the paracrine manner as shown across in vitro assessment.…”
Section: Rosmarinic Acidmentioning
confidence: 99%
“…Besides this, it also attenuates cardiac fibrosis in long-term pressure overload via AMPKα/Smad3 Signalling (Zhang et al, 2018). Yao et al (2019) reported that rosmarinic acid inhibits NLRP3 inflammasome activation, resulting in reduced CRP generation in vascular smooth muscle cells. Rosmarinic acid also alleviated cardiomyocyte apoptosis by inhibiting the expression and release of Fas L in cardiomyoblast via the paracrine manner as shown across in vitro assessment.…”
Section: Rosmarinic Acidmentioning
confidence: 99%
“…RA has been widely studied due to its remarkable biological and pharmacological activities, including anti-microbial, antioxidant and anti-inflammatory properties [20]. Until now, only a limited number of studies have dealt with the effect of RA on NLRP3-inflammasome [21,22,23], and none of them on human immortalized HaCaT keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of genome-wide association studies has identified NLRP3 as a predictor of CRP levels (Dehghan et al, 2011). A recent study revealed that rosmarinic acid inhibits nicotine-induced AS by suppressing the ROS-NLRP3 inflammasome-CRP axial (Yao et al, 2018). These reports suggest a link between increased levels of CRP and the NLRP3 inflammasome, and thus, a link to AS.…”
Section: Introductionmentioning
confidence: 99%